التقشير الكيميائي - دلول محمود; الخير عبد الله; الخير عبد الله; سليطين عامر (Latakia University Journal -Medical Sciences Series, 2019)
يشكل الكلف والنمش وندب العد الشائع مشاكل طبية وجمالية شائعة. في دراستنا استخدمنا التقشير الكيميائي السطحي لمعالجة هذه المشاكل. تضمنت دراستنا 56 مريضاً موزعين حسب الشكوى السريرية كما يلي: كلف 34 مريضاً. نمش 8 مرضى. ندب عد شائع 14 مريضاً. قسمنا المرضى حسب كل شكوى إلى مجموعتين متساويتين. طبقنا التقشير الكيميائي السطحي باستخدام محلول جسنر على المجموعة الأولى, بينما طبقنا التقشير الكيميائي السطحي باستخدام حمض الغلكوليك70% على المجموعة الثانية. قمنا بدراسة الفعالية والاختلاطات لكل من المادتين المقشرتين السابقتين, ثم قارنا بينهما. وبالنتيجة وجدنا أن: - التقشير الكيميائي السطحي باستخدام محلول جسنر أو حمض الغليكوليك 70 % فعال في معالجة الكلف والنمش وندب العد الشائع الخفيفة وذلك بنسبة اختلاطات قليلة. - محلول جسنر مساو تقريباً لحمض الغليكوليك 70 % بالفعالية والاختلاطات. - ندب العد الشائع العميقة لا تستجيب لهذه المعالجة. Melasma, freckles, and acne vulgaris scars are common medical and aesthetic problems. In our research, we used superficial chemical peeling to treat these problems. The research included 56 patients distributed according to the clinical compliant as follows: Melasma 34 patients. Freckles 8 patients. Acne scars 14 patients. We divided the patients into two equal groups according to clinical compliant. We applied superficial chemical peeling using Jessner’s solution to the first group, while superficial chemical peeling using glycolic acid 70 % was applied to the other groups. We found out that superficial chemical peelig using Jessner’s solution or glycolic acid 70 % is effective in the treatment of melasma, freckles, and superficial acne scars, with a low percentage of complications. Jessner’s solution is almost equal to glycolic acid 70 % in efficacy and complications. But deep acne scars do not respond to this treatment.